Analisis Kepuasan Aplikasi ULA (Untung Lancar Aman) Metode UTAUT Pada UMKM Jombang: Analysis of ULA Application Satisfaction (Profit Smoothly Safe) UTAUT Method in Jombang MSMEs - Kaasto, Darojat; Murtadho, Mohamad Ali; Wafa, Moh. Shohibul (Computech : Jurnal Ilmiah Teknologi Informasi dan Komunikasi, 2024)
Information systems have become an urgent need for society, including Micro, Small and Medium Enterprises (MSMEs) who are online or e-commerce traders. One e-commerce that makes things easy for MSMEs is the presence of the ULA (Lucky Current and Safe) application which is managed by PT Jembatan Akar Teknologi. The ULA application is a multi-category B2B e-commerce marketplace that combines technology, capabilities and modern retail equipment for MSMEs. In this research, researchers used the UTAUT method to determine the response and perspective of user success and satisfaction with a system when applied to users of the ULA application which is aimed at MSMEs in Jombang City. The type of approach in this research is quantitative by distributing questionnaires online and offline to 80 respondents which are processed with SPSS16 software. Based on data processing, the results showed that the level of user satisfaction with the ULA application in Jombang had been achieved only on the Facilitating Conditions variable, but had not yet been achieved on the Performance Expectancy, Performance Expectancy and Social Influence variables. The level of user satisfaction in the Facilitating Conditions factor meets the indicators of the convenience of a condition that makes things easier for users and is in accordance with the needs of ULA application users in Jombang. Hypothesis testing shows that each UTAUT variable can influence user satisfaction with the ULA application. Kata Kunci : Information Systems, MSMEs, User Satisfaction, ULA Application, UTAUT, PT Jembatan Akar Teknologi.